Forces on fixed offshore structures: effects of nonlinear irregular wave kinematics - Ismail, Muhammad Izzuddin (Universiti Teknologi PETRONAS, 2017)
Forces from a nonlinear irregular wave model on a offshore structure are investigated. Comparing the results obtained from the linear wave theory and with the stream function wave theory and investigate the force from fully nonlinear irregular waves is used from the Morison’s equation. The predictions of the wave forces is compared. The corresponding force profiles from the stream function theory with the force-profiles of two selected waves from the irregular wave train are compared. The results recommend that the non-linear irregular waves give high value to larger extreme wave forces that those predicted by linear theory. The linear theory which is stream function theory in some issue underestimate the wave forces acting on the offshore structure.